Reactive consolidation and high-temperature strength of HfB2–SiB6. Issue 12 (September 2022) - Demirskyi, D.; Nishimura, T.; Suzuki, T.S.; Yoshimi, K.; Vasylkiv, O.
Abstract: During the spark plasma sintering at 1900 °C, SiB6 decomposes into cubic silicon carbide and boron carbide, owing to the reducing environment of the furnace. For the HfB2 -SiB6 ceramic improvement in hardness (24.5 ± 0.7 GPa) was attributed to the formation of the B12 (C, Si, B)3 . Fracture toughness by indentation (6.8 ± 2.4 MPa·m 1/2 ), single-edge notched bend specimens (4.6 ± 0.4 MPa·m 1/2 ) and room-temperature strength (513 ± 21 MPa) of the HfB2 –SiB6 composite produced by spark plasma sintering was higher or on the same level as the HfB2 –SiC ceramics. The high-temperature flexural strength tests suggested that the strength would decrease monotonically with an increase in temperature. At or below 1600 °C, only a linear stress-strain response was observed, and resulted into a mean strength of ~320 MPa. During the tests at 1800 °C, we observed a nonlinear deformation indicating ongoing plastic deformation which led to a strength decrease down to 230 ± 30 MPa.